UPAYA PEMBINAAN PEMERINTAH KABUPATEN BANYUWANGI DALAM MENANGGULANGI KAUM MISKIN KOTA DI KECAMATAN BANYUWANGI - Lia Muniati, Vina; Rahayu, Sri; Imaniar, Dimas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2025)
The issues in this research are related to the high poverty rate in the Banyuwangi District, particularly experienced by street vendors, buskers, and street children.The existence of this group reflects a complex social challenge that demands serious attention and handling from the local government.The purpose of the research is to analyze the coaching efforts undertaken by the Banyuwangi Regency Government in addressing the issues faced by the urban poor.The research also identifies the obstacles that arise during the implementation of community welfare improvement programs.The methodology used was a descriptive qualitative approach.Data collection techniques were carried out through in-depth interviews with key informants and direct field observations.Data analysis includes the processes of reduction, presentation, and conclusion drawing to obtain an objective and comprehensive picture.The research results show that government programs have not been fully effective in addressing poverty.The low level of public awareness and the limited capacity of human resources are the main obstacles in the implementation of policies.The community feels that the services provided do not meet their expectations.The conclusion of this research underscores the importance of enhancing the capacity of bureaucratic resources and improving program governance.Strengthening communication between the government and the community is also necessary to ensure that policies are more targeted.More effective implementation is expected to drive sustainable improvement in community welfare.